The Effect of Tummy Time Exercise on Gross Motor Skills in Babies Aged 3-6 months - Apriyani Hastuti; Diah Nawang Wulan; Bayu Budi Laksono; Ardhiles Wahyu Kurniawan; Sa Sa Aung (Universitas Nahdlatul Ulama Surabaya, 2026)
Tummy time exercise involves positioning the baby on their stomach, allowing them to support their body weight. The purpose of this study was to determine the effect of tummy time exercise on gross motor skills in babies aged 3-6 months. This research design employed analytics using a One-Group Pretest-Posttest Design approach. The population consisted of 43 babies aged 3-6 months at the Integrated Health Service Post, known as Posyandu, in Arjowilangun Village, Malang Regency. The sampling technique was a total sampling. The time of intervention was 2 weeks. Data analysis employed the Wilcoxon Signed Ranks Test. Before giving tummy time exercise intervention, most respondents had normal gross motor skills (97.7%), and a small proportion had delayed gross motor skills (2.3%). After intervention, all respondents had advanced gross motor skills (100%). Based on the results of the Wilcoxon Signed Rank Test, there was a significant influence on gross motor skills in babies aged 3-6 months before and after the intervention, as indicated by a p-value of 0.000 and a calculated z-value of -6.487. In conclusion, tummy time exercises can significantly increase gross motor skills in babies aged 3-6 months. Parents should apply tummy time exercises to babies regularly to promote the development of gross motor skills in babies aged 3-6 months, enabling them to achieve gross motor milestones more quickly.